Between Administrative and Constitutional Jurisdiction: Investigating Dual Pathways to Justice in Indonesia - Ainuddin , Ainuddin (Institute for Law and Economics Studies, 2025)
This study explores the intersection of administrative and constitutional adjudication in Indonesia, focusing on the overlapping jurisdictions of the State Administrative Court (PTUN) and the Constitutional Court (MK). Although these institutions were established to complement one another within a system of checks and balances, their concurrent mandates often generate legal uncertainty and procedural inefficiencies. Employing normative legal research and a conceptual framework, the analysis examines primary sources (the 1945 Constitution, PTUN Act, Constitutional Court Act, Government Administration Act), secondary literature, and illustrative case law. Through statutory, conceptual, and case‐based approaches, the study identifies points of convergence and divergence in the courts’ competencies, as well as the practical implications for citizens seeking redress. The findings reveal that PTUN’s focus on concrete administrative acts and the MK’s review of abstract legal norms can lead to contradictory outcomes: a PTUN judgment may vindicate a claimant without invalidating the underlying statute, while an MK annulment of a norm does not automatically reverse prior administrative decisions. This dual‐track system imposes duplicative litigation burdens, prolongs resolution timelines, increases costs, and ultimately erodes public confidence in the rule of law. To resolve the overlapping jurisdictions between PTUN and MK, this study recommends clearer statutory delineation of competencies, coordinated case-management protocols, and the possible establishment of a unified forum for disputes with both administrative and constitutional dimensions. Strengthening institutional synergy through capacity building and enhancing transparency in jurisdictional guidance are also essential to ensure consistency, reduce litigation burdens, and restore public trust in the rule of law